Magnetic resonance perfusion imaging in patients with coronary artery disease: a qualitative approach - Sensky, Penelope R.; Samani, Nilesh J.; Reek, Christine; Cherryman, Graham R. (The International Journal of Cardiovascular Imaging, 2002)
Although contrast-enhanced first pass magnetic resonance imaging (MRI) has potential to quantify blood flow through extensive image post-processing, clinical utility is likely to depend on rapid qualitative analysis. To investigate use of an on-line analytical approach for detection of coronary artery disease (CAD). Thirty subjects with CAD underwent contrast-enhanced rest/adenosine stress MRI with basal, mid-papillary and apical short-axis image acquisition. Each short axis was divided into eight regions of interest (ROI). Regional perfusion was visually classified as normal or impaired according to transmural distribution and defect reversibility. MRI and angiographic data were compared. Qualitative MRI reporting was possible for 98% ROI. Eighty-six coronary artery (CA) territories were assessed of which 71 (83%) had stenoses. Sensitivity and specificity for detection of stenoses were 93 and 60%, respectively. The proportion of hypoperfused ROI rose from 31% with < 50% stenosis to 65% with occlusion. More transmural defects were seen in infarction-related territories (75 vs. 54%, p < 0.05). More ROI demonstrated defect reversibility in occluded rather than in stenosed infarction-related vessels (89 vs. 58%, p < 0.05). Occluded vessels with grade 2-3 collaterals contained a higher proportion of normal ROI (44 vs. 25%, p < 0.05). Qualitative MRI analysis had high sensitivity and moderate specificity for detecting CA stenoses. Additional information was obtained relating to lesion severity, previous infarction, myocardial viability and impact of collateral circulation. The technique has potential for de novo diagnosis of CAD and as a complementary modality to angiography to assess the significance of given angiographic lesions.